Degradação Ambiental Agropecuária na América Latina: Uma Abordagem de Índices nos Países da Região - Nelson Guilherme Machado Pinto (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
The changes occurring in the environment accompany the evolution of the human being as a social being. However, some of these changes have been causing problems for society. In this context, environmental degradation appears as a great challenge for several countries. A set of causes is pointed out as responsible for the current process of degradation, however, in the Latin American scenario, this issue has a large part originating from the agricultural exploration. This study aims to analyze the pattern of agricultural environmental degradation of Latin America. The measurement of degradation occurs by the construction of an Agricultural Environmental Degradation Index (Aedi), which is used as a proxy to determine the degradation of an area caused by farming. In the construction of the Aedi, it was found that some regions and states have a very high degradation pattern. Regarding the Latin American countries studied, the average value of the index was 8.25%. The countries with the highest levels of environmental degradation were Brazil, Argentina and Mexico, because the economies of these countries are strongly based on agriculture. In this sense, to chance this situation, the government should interfere more and there should be a greater awareness of farmers in countries that had higher levels of degradation. The lowest degradation rates were from countries where the agricultural activity does not have high levels of productivity, such as Nicaragua, Chile and El Salvador.